Diffuse Decreased Gray Matter in Patients with Idiopathic Craniocervical Dystonia: A Voxel-Based Morphometry Study - Piccinin, Camila C.; Piovesana, Luiza G.; Santos, Maria C. A.; Guimarães, Rachel P.; De Campos, Brunno M.; Rezende, Thiago J. R.; Campos, Lidiane S.; Torres, Fabio R.; Amato-Filho, Augusto C.; França, Marcondes C.; Lopes-Cendes, Iscia; Cendes, Fernando; et al. (Frontiers in Neurology, 2015)
Background: Recent studies have addressed the role of structures other than the basal ganglia in the pathophysiology of craniocervical dystonia. Neuroimaging studies have attempted to identify structural abnormalities in craniocervical dystonia but a clear pattern of alteration has not been established. We performed whole brain evaluation using voxel-based morphometry to identify patterns of gray matter changes in craniocervical dystonia. Methods: We compared 27 patients with craniocervical dystonia matched in age and gender to 54 healthy controls. Voxel-based morphometry was used to compare gray matter volumes. We created a two-sample t-test corrected for subjects’ age and we tested with a level of significance of p<0.001 and false discovery rate correction (p<0.05). Results: Voxel-based morphometry demonstrated significant reductions of gray matter using p<0.001 in the cerebellar vermis IV/V, bilaterally in the superior frontal gyrus, precuneus, anterior cingulate and paracingulate, insular cortex, lingual gyrus and calcarine fissure; in the left hemisphere in the supplemementary motor area (SMA), inferior frontal gyrus, inferior parietal gyrus, temporal pole, supramarginal gyrus, rolandic operculum , hippocampus, middle occipital gyrus, cerebellar lobules IV/V, superior and middle temporal gyri; in the right hemisphere, the middle cingulate and precentral gyrus. Our study did not report any significant result using the false discovery rate correction. We also detected correlations between gray matter volume and age, disease duration, duration of botulinum toxin treatment and the Marsden-Fahn dystonia scale scores. Conclusions: We detected large clusters of gray matter changes chiefly in structures primarily involved in sensorimotor integration, motor planning, visuospatial function and emotional processing.